Efektivitas Pengelolaan Badan Usaha Milik Desa (BUMDes) Dalam Meningkatkan Ekonomi Masyarakat Desa Serumpun Jaya Ditinjau Dari Perspektif Ekonomi Syariah - Ayu Anggraini; Viras Alti Pidola (Journal of Islamic Economic and Law (JIEL), 2025)
Village-Owned Enterprises (BUMDes) serve as a strategic instrument in rural economic development, aiming to improve community welfare through the management of local potential. However, in practice, many BUMDes have not demonstrated optimal performance due to weak governance, low community participation, and insufficient application of Islamic economic principles as foundational values. This study aims to analyze the effectiveness of the management of BUMDes Jaya Bersama in improving the economy of the Serumpun Jaya village community from an Islamic economic perspective. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The results of the observation indicate that the effectiveness of BUMDes Jaya Bersama’s management falls into the “less optimal” category, with an implementation rate of 57.1%. Interview findings reveal that the management has incorporated principles such as cooperation, participation, emancipation, transparency, accountability, and sustainability. However, the application of Islamic economic principles—such as justice, honesty, transparency, and the avoidance of usury (riba)—has not been fully understood or consistently implemented by all administrators and the community.Factors influencing the effectiveness of BUMDes include community participation, human resource capacity, planning and evaluation systems, and information transparency. The conclusion of this study indicates that although BUMDes Jaya Bersama has made efforts to fulfill its role, improvements in governance and the comprehensive integration of Islamic values are still necessary to promote the village's economic independence.